2021
DOI: 10.1088/2053-1591/abfac5
|View full text |Cite
|
Sign up to set email alerts
|

Research on static recrystallization behaviour of pure molybdenum rods during forging

Abstract: In this work, thermal compression experiment of pure molybdenum rods with sintered density of 9.7–9.8 g cm−3 were performed on the Gleeble-1500D thermal simulator. The double-pass vacuum high-temperature compression test was carried out in a deformation temperature of 1200 °C–1350 °C, a strain rate of 3 s−1 and an interval time of 10–500 s. The stress-strain curve was obtained and analysed. The static softening rate was calculated by the 2% compensation method of yield stress, and the curve of that was fitted.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…where q q 1 4 ~are material constants. Combining equations ( 7) and (8), equation ( 9) can be obtained as below: According to equation (9), the parameters in the static softening kinetics model can be calculated by multiple nonlinear regression. Equation (10) displays the calculated results.…”
Section: = --mentioning
confidence: 99%
See 1 more Smart Citation
“…where q q 1 4 ~are material constants. Combining equations ( 7) and (8), equation ( 9) can be obtained as below: According to equation (9), the parameters in the static softening kinetics model can be calculated by multiple nonlinear regression. Equation (10) displays the calculated results.…”
Section: = --mentioning
confidence: 99%
“…For static softening behaviors, Ding et al [8] analyzed the effects of external stress on the static recovery (SRV) mechanism of A5083 aluminum alloy, and found that the effects of interrupted strain on SRV depend on the external stress during the inter-pass holding process. Zhang et al [9] studied the effects of deformation temperature and holding time on the static recrystallization (SRX) softening behaviors of pure molybdenum, and established a SRX kinetics model. Xu et al [10] explored the effects of different deformation and inter-pass holding parameters on the metadynamic recrystallization softening (MDRX) behaviors of V-containing 12Cr rotor steel, and constructed an MDRX kinetics model.…”
Section: Introductionmentioning
confidence: 99%